Superior p‐Type Surface Doping of Cubic Boron Nitride via MoO3 Adsorption. Issue 4 (3rd February 2022) - Liu, Yaning; Zhang, Qiuxia; Zhang, Xin; Gao, Nan; Li, Hongdong
Abstract: Cubic boron nitride (c‐BN) is a potential candidate material for electronic and optoelectronic devices under extreme conditions, while the difficulty in conventional doping severely hinders its applications. Herein, by first‐principles calculation, an efficient p‐type doping on the c‐BN surface (areal hole density of 8.82 × 10 13 cm −2 and hole mobility of 826 cm 2 V −1 s −1 at room temperature) is realized by the surface charge transfer mechanism with the MoO3 molecule having a high electron affinity as the dopant. The MoO3 molecule draws electrons from the c‐BN, making the hole accumulation on the c‐BN surface. The areal hole density of c‐BN enhances with the increase of MoO3 molecule density and reaches the maximum (1.24 × 10 14 cm −2 ) with MoO3 monolayer adsorption. The optical absorption coefficient significantly increases in the infrared and visible regions. The superior p‐type doping for c‐BN is also achieved by adsorbing transistor metal oxides with the high electron affinity values (such as ReO3, CrO3, WO3, and V2 O5 ). This study opens a novel avenue for promoting c‐BN applied in optoelectronic devices. Abstract : By first‐principles calculation, the superior p‐type surface doping on the c‐BN (100) surface is achieved by surface charge transfer mechanism with the MoO3 molecule having a large electron affinity as the dopant. The areal hole density of c‐BN enhances with the increasing of molecule density. The optical absorption coefficient significantly increases in the infrared and visible regions.